2009
DOI: 10.1186/1471-2180-9-245
|View full text |Cite
|
Sign up to set email alerts
|

Some putative prebiotics increase the severity of Salmonella entericaserovar Typhimurium infection in mice

Abstract: BackgroundPrebiotics are non-digestible food ingredients believed to beneficially affect host health by selectively stimulating the growth of the beneficial bacteria residing in the gut. Such beneficial bacteria have been reported to protect against pathogenic infections. However, contradicting results on prevention of Salmonella infections with prebiotics have been published. The aim of the present study was to examine whether S. Typhimurium SL1344 infection in mice could be prevented by administration of die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…One example of this is a study showing that an increase in Bifidobacterium in ob/ob mice due to prebiotic treatment resulted in a decrease in gut permeability. 32 However, several studies [15][16][17][18]33,34 also observe increased Salmonella translocation and/or infection in rodents in vivo following intake of bifidogenic oligosaccharides, which could be caused by a reduction in epithelial integrity in the gut, as shown by Ten Bruggencate et al 17 We speculate that any negative correlation between Bifidobacterium and TER may be connected to metabolic cross-feeding between different bacterial groups, resulting in changed abundances of other bacteria that may influence TER. Such effects will not be revealed in in vitro fermentation models based on bifidobacterial monocultures.…”
Section: Discussionmentioning
confidence: 91%
“…One example of this is a study showing that an increase in Bifidobacterium in ob/ob mice due to prebiotic treatment resulted in a decrease in gut permeability. 32 However, several studies [15][16][17][18]33,34 also observe increased Salmonella translocation and/or infection in rodents in vivo following intake of bifidogenic oligosaccharides, which could be caused by a reduction in epithelial integrity in the gut, as shown by Ten Bruggencate et al 17 We speculate that any negative correlation between Bifidobacterium and TER may be connected to metabolic cross-feeding between different bacterial groups, resulting in changed abundances of other bacteria that may influence TER. Such effects will not be revealed in in vitro fermentation models based on bifidobacterial monocultures.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study comparing the gut microbiome of adults from different continents (Africa, North and South America) confirmed large variations among Americans, Europeans and Africans. Prebiotics are generally recognized to enhance the barrier effect of the gut microbiota toward enteropathogens, but few studies with animal models have shown that prebiotics, especially inulin and FOSs, could promote Salmonella growth, translocation or virulence [40][41][42][43]. Carbohydrates in the diet could, therefore, contribute to the large variation observed for gut microbiota composition [1 && ].…”
Section: Carbohydrates Shape the Human Gut Microbiotamentioning
confidence: 99%
“…However, prebiotic supplementation with nutrients thought to promote in vivo growth of Bifidobacteria and Lactobacilli did not inhibit S . Typhimurium colonization in vivo , but instead increased pathogen colonization when compared to mice fed a standard diet [10]. These studies indicate that identification of beneficial microbiota communities, and the nutrients that shape their composition, may be incomplete or not specific enough.…”
Section: Barrier Function Of the Host Microbiotamentioning
confidence: 99%